Sourcing Stability in a Time of Climate Change. (1st April 2014) - Shockley, Kenneth; Light, Andrew
Abstract : Anthropogenic climate change poses a direct and imminent threat to the stability of modern society. Recent reports of the probable consequences of climate change paint a grim picture; they describe a world environmentally much less stable than the world to which we have become accustomed. As we begin to adapt to our changing climate, we will need to identify new sources for the stability necessary for a flourishing society. I suggest that this stability should come from the ideals of the good life we seek to promote when we focus on capabilities, on the substantial freedoms humans need to flourish. These ideals serve as a stable foundation for well-being in a time of great environmental and social instability; they should serve as guides for our policies, practices and institutions. I conclude by appealing to capabilities as a means of integrating well-being into our adaptation strategies, and show how doing so may well provide a way of formulating a powerful moral justification for adaptation strategies appropriate for both the developed and the developing world.